Correction to the article “Contralateral Upper Limb Weakness Following Botulinum Toxin A Injection for Poststroke Spasticity”, published on Acta Med Port 2020 Nov;33(11):761-764 - de Sousa, Carla (2020)
On page 761, in the first sentence of the Introduction, where it reads: ”Cardiovascular Botulinum toxin A (BoNT-A) has beenapproved for spasticity management.”It should read: “Botulinum toxin A (BoNT-A) has been approved for spasticity management.”Article published with errors: https://www.actamedicaportuguesa.com/revista/index.php/amp/article/view/11503